1998
DOI: 10.1111/j.1746-1561.1998.tb06348.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a High School Program to Increase Fruit and Vegetable Consumption: Gimme 5 — A Fresh Nutrition Concept for Students

Abstract: This paper describes an intervention to increase high school students' fruit and vegetable consumption. Twelve schools were randomized to intervention or control conditions. The cohort (2,213 students; 56% females, 84% Caucasian) were followed from 9th to 12th grades. Interventions comprised a media campaign, classroom workshops, school meal modification, and parental support. Usual daily servings of fruit/vegetables increased 14% in the intervention compared to the control group (p > 0.001) the first three ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
102
0
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(110 citation statements)
references
References 11 publications
4
102
0
4
Order By: Relevance
“…A study in Minnesota, USA, demonstrated a significant increase in observed lunchroom intake of fruit and vegetables, and an overall increase in reported fruit consumption, but not vegetable consumption, among fourth and fifth graders (26). Similarly, a 14% increase in the usual daily servings of vegetables and fruit was observed for a high-school programme, but this effect disappeared by year 3 (27).…”
Section: Discussionmentioning
confidence: 99%
“…A study in Minnesota, USA, demonstrated a significant increase in observed lunchroom intake of fruit and vegetables, and an overall increase in reported fruit consumption, but not vegetable consumption, among fourth and fifth graders (26). Similarly, a 14% increase in the usual daily servings of vegetables and fruit was observed for a high-school programme, but this effect disappeared by year 3 (27).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the multicomponent programme is relatively low in cost, but takes a lot of classroom time, and is labourintensive to put into practice 7,25 -27 . Also a lack of adoption or (loyal) implementation of curricula due to time constraints has been reported 28 . A free distribution, on the other hand, is easier to implement because it becomes a daily routine, but is far more expensive compared with a multicomponent programme.…”
Section: Discussionmentioning
confidence: 99%
“…Nicklas et al(1998) 25 described an intervention programme involving a media campaign, classroom workshops, school meal modification, and parental support. This was implemented in 12 high schools with a total of 2,213 students.…”
Section: Variable Significance (Sig)mentioning
confidence: 99%